2008
DOI: 10.1007/s10237-008-0137-y
|View full text |Cite
|
Sign up to set email alerts
|

Probing the influence of myelin and glia on the tensile properties of the spinal cord

Abstract: Although glia have been historically classified as the structurally supporting cells of the central nervous system, their role in tissue mechanics is still largely unstudied. The influence of myelin and glia on the mechanical properties of spinal cord tissue was examined by testing embryonic day 18 chick embryo spinal cords in uniaxial tension following disruption of the glial matrix using either ethidium bromide (EB) or an antibody against galactocerebroside (alphaGalC) in the presence of complement. Demyelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…Indeed, even if it has been shown that both neurons and glial cells are very soft (Lu et al 2006), recent works have demonstrated that demyelination significantly lowers axonal stiffness and ultimate tensile stress (Shreiber et al 2008). It is then probable that myelin sheaths mechanically protect axons both during Klingler's preparation and dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even if it has been shown that both neurons and glial cells are very soft (Lu et al 2006), recent works have demonstrated that demyelination significantly lowers axonal stiffness and ultimate tensile stress (Shreiber et al 2008). It is then probable that myelin sheaths mechanically protect axons both during Klingler's preparation and dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of protective myelin of the NRs (Shreiber et al 2009), recent findings highlighting the primordial role of blast-damaged ion channels in neurobehavioral deficits (Park et al 2013), and the Na v leak observed during trauma (Wang et al 2009) suggest the need for a strain-based damage criterion specific to the ion channels' properties. This Na v (and in this model, K v ) leak has been rationalized by a hyperpolarizing shift (or left-shift) of transient current operational range (Wang et al 2009) in the conductance of the ion channel.…”
Section: Damage Coupling Modelmentioning
confidence: 99%
“…Despite observations of stress concentrations at the NRs during stretch injury, the relation between axonal, myelin and glial stiffnesses, as well as the role of oligodendrocytes and paranodal axo-glial adhesions in the "glueing" of all three components remain largely controversial (Shreiber et al 2009). As a consequence and in the absence of more conclusive evidences, the case where all the strain is sustained equally by the NRs and the IRs is considered here (i.e., v = x).…”
Section: Calibrationmentioning
confidence: 99%
“…Even on a larger scale, this result seems to hold 61 . The difference between white and grey matter might stem from the lower cell density in the former 53 , which is structurally dependent on the oligodendrocyte connectivity, because demyelination in the rat spinal cord leads to lower stiffness and tensile stress 62 . Lower stiffness has also been reported for demyelinated regions in the murine brain parenchyma measured with magnetic resonance elastography (MRE) 63 .…”
Section: Tissue Considerationsmentioning
confidence: 99%